1995
DOI: 10.1227/00006123-199510000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Effectiveness of Brain Arteriovenous Malformation Embolization Using Acrylic and Particles

Abstract: The purpose of this article is to report on the safety and effectiveness of brain arteriovenous malformation (AVM) embolization for two series of patients, of which one was treated with particulate embolization and the other with acrylic embolization. Sixty-five consecutive patients from embolization logs and patient records from 1988 to 1993 were reviewed. AVMs were routinely treated with particulate embolization early in the review (1988-1991), and after a transition period, the technique was changed to acry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Thanks to the improvement of endovascular materials and experience, endovascular therapy has become increasingly important in 51 the management of cerebral AVMs. The main goals of AVM embolization are nidus reduction before surgery or radiosurgery, curative embolization, and palliative embolization 3,25,[27][28] . Since the pioneers in the early 1960s reported using methyl methacrylate to embolize the feeding pedicle to treat AVMs, a considerable evolution of microcatheter tools, embolization materials and techniques has proved the success of embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the improvement of endovascular materials and experience, endovascular therapy has become increasingly important in 51 the management of cerebral AVMs. The main goals of AVM embolization are nidus reduction before surgery or radiosurgery, curative embolization, and palliative embolization 3,25,[27][28] . Since the pioneers in the early 1960s reported using methyl methacrylate to embolize the feeding pedicle to treat AVMs, a considerable evolution of microcatheter tools, embolization materials and techniques has proved the success of embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Onyx is a new embolization material that has gradually been adopted for AVM embolization during the past decade, and some authors have already reported their initial experiences in the treatment of AVMs with Onyx [11][12][5][6][7][8][9][10][11][12][13][14][15][16]19,21,23,[25][26][27][28] . As mentioned in these articles, Onyx is a nonadhesive agent with controllable endovascular behavior, which allows more precise nidus penetration creating a solid cast, the overall initial complete obliteration rate of intracranial AVMs with Onyx is rela-tively high compared with that of other embolic agents 7,28 . Despite improvements in endovascular techniques and embolic agents, the complication profile of brain AVM embolization is of concern and not well described [2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
“…If an intranidal microcatheter tip location can be found, the injection of NBCA is optimal. 3,28,29 With this material, however, there is always a risk of permanently gluing the catheter tip within the cerebral vessel. Also commonly used for embolization of cerebral AVMs, PVA will not provide permanent embolization, and closing large fistulas is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Silk sutures pose less of a hindrance to surgery than other agents such as microcoils or NBCA. 15,20,28 The disadvantage of silk as an embolic agent is its radiolucency. 9,30 The incidence of endovascular embolization-induced delayed hemorrhage is not frequent and ranges from 3 to 5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation